2020
DOI: 10.1186/s12929-019-0614-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNAs in antiviral responses to dengue infection

Abstract: Dengue virus (DENV) is the etiological agent of dengue fever. Severe dengue could be fatal and there is currently no effective antiviral agent or vaccine. The only licensed vaccine, Dengvaxia, has low efficacy against serotypes 1 and 2. Cellular miRNAs are post-transcriptional regulators that could play a role in direct regulation of viral genes. Host miRNA expressions could either promote or repress viral replications. Induction of some cellular miRNAs could help the virus to evade the host immune response by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 110 publications
1
52
0
Order By: Relevance
“…For example, MRX34, a microRNA (miRNA) mimic, has reached phase 1 studies in patients with advanced solid tumors, including hepatocellular carcinoma, pancreatic cancer and cholangiocarcinoma (22). miR-146a may serve as a promising therapeutic target for dengue (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, MRX34, a microRNA (miRNA) mimic, has reached phase 1 studies in patients with advanced solid tumors, including hepatocellular carcinoma, pancreatic cancer and cholangiocarcinoma (22). miR-146a may serve as a promising therapeutic target for dengue (23).…”
Section: Discussionmentioning
confidence: 99%
“…For example, MRX34, a microRNA (miRNA) mimic, has reached phase 1 studies in patients with advanced solid tumors, including hepatocellular carcinoma, pancreatic cancer and cholangiocarcinoma ( 22 ). miR-146a may serve as a promising therapeutic target for dengue ( 23 ). Wheatley et al ( 24 ) previously developed a DNA vaccine vector co-expressing an miRNA designed in silico miRNA to inhibit PERK with a HIV-1 envelope.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest is the possibility that nucleotide sequences from the 5'UTR are crucial in enabling YFV to propagate in primates and/or mosquitoes. Although no experiments have thus far reported systematically investigating the constancy of nucleotides in the 5'UTR, the effectiveness of the varieties of small interfering RNA in the control of virus infection is a field of active investigation (21)(22)(23)(24)(25). Should suitable conditions be found in which 5'UTR nucleotide sequences are determined to be inhibitory to YFV, parenteral delivery methods of the relevant inhibitory nucleotides would need to be developed to achieve a therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…RNA interference (RNAi) is an important antiviral defense response in plants and invertebrates [176]. In DENV infection, knockdown of these components resulted in increased DENV replication in mammalian cells, suggesting that the RNAi pathways may play important roles in the cellular anti-DENV responses [177,178]. Additional evidence showed that DENV can interfere with RNAi pathways in human hepatocytes cells via NS4B and subgenomic flavivirus RNA (sfRNA) interactions with Dicer's ability to process small Please use Adobe Acrobat Reader to read this book chapter for free.…”
Section: Denv Infection and The Host Innate Immune Responsesmentioning
confidence: 99%